Synthesis and Properties of High Strength Thin Film Composites of Poly(ethylene Oxide) and PEO-PMMA Blend with Cetylpyridinium Chloride Modified Clay. (19th August 2015) - Khan, Mohammad Saleem; Sultana, Sabiha
Abstract : Ion-conducting thin film composites of polymer electrolytes were prepared by mixing high MW poly(ethylene oxide) (PEO), poly(methyl methacrylate) (PMMA) as a polymer matrix, cetylpyridinium chloride (CPC) modified MMT as filler, and different content of LiClO4 by using solution cast method. The crystallinity, ionic conductivity (σ ), and mechanical properties of the composite electrolytes and blend composites were evaluated by using XRD, AC impedance, and UTM studies, respectively. The modification of clay by CPC showed enhancement in the d -spacing. The loading of clay has effect on crystallinity of PEO systems. Blend composites showed better mechanical properties. Young's modulus and elongation at break values showed increase with salt and clay incorporation in pure PEO. The optimum composition composite of PEO with 3.5 wt% of salt and 3.3 wt% of CPMMT exhibited better performance.